Contrast Tempo of Movement and Its Effect on Power Output and Bar Velocity During Resistance Exercise - Wilk, Michal; Jarosz, Jakub; Krzysztofik, Michal; Filip-Stachnik, Aleksandra; Bialas, Marcin; Rzeszutko-Belzowska, Agata; Zajac, Adam; Stastny, Petr (Frontiers in Physiology, 2021)
This study was evaluate the effects of contrast movement tempo (fast vs slow) on power output and bar velocity during the bench press exercise. Ten healthy men (age = 26.9 ± 4.1 years; body mass = 90.5 ± 10.3 kg; bench press 1RM = 136.8 ± 27.7 kg) with experience in resistance training (9.4 ± 5.6 years) performed the bench press exercise under three conditions: with explosive tempo of movement in each of three repetitions (E/E/E = explosive, explosive, explosive); with slow tempo of movement in the first repetition and explosive in the next two repetitions (S/E/E = slow, explosive, explosive); and with a slow tempo of movement in the first two repetitions and explosive tempo in the last repetition (S/S/E = slow, slow, explosive). The slow repetitions were performed with a 5/0/5/0 (eccentric/isometric/concentric/isometric) movement tempo, while the explosive repetitions were performed with an X/0/X/0 (X- maximal speed of movement) movement tempo. During each experimental session, the participants performed one set of three repetitions at 60%1RM. The one-way repeated measures ANOVA showed a statistically main effect for PP (p = 0.04; η2 = 0.30) and PV (p = 0.03; η2 = 0.32). The post hoc analysis revealed that PP was significantly higher for E/E/E compared with S/S/E (p = 0.03; ES = 0.58). Further the post hoc analysis revealed that PV was significantly higher for E/E/E compared with S/S/E (p = 0.03; ES = 0.47).The main finding of this study was that the different distribution of movement tempo during a set has a significant impact on power output and bar velocity in the bench press exercise at 60%1RM. Therefore, the use of one slow repetition at the beginning of a set does not decrease the level of power output in the third repetition.